Pharmacokinetic and Pharmacodynamic Effects of a γ‐Secretase Modulator, PF‐06648671, on CSF Amyloid‐β Peptides in Randomized Phase I Studies. Issue 1 (11th September 2019) - Ahn, Jae Eun; Carrieri, Charles; Dela Cruz, Fernando; Fullerton, Terence; Hajos‐Korcsok, Eva; He, Ping; Kantaridis, Constantino; Leurent, Claire; Liu, Richann; Mancuso, Jessica; Mendes da Costa, Laure; Qiu, Ruolun
Abstract : γ‐Secretase modulators (GSMs) represent a promising therapy for Alzheimer's disease by reducing pathogenic amyloid‐β (Aβ) peptide production. Three phase I studies (NCT02316756, NCT02407353, and NCT02440100) investigated the safety/tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of the oral GSM, PF‐06648671. A PK/PD indirect‐response model was developed (using biomarker data) to simultaneously characterize differential effects of PF‐06648671 on multiple Aβ species in cerebrospinal fluid (CSF). Healthy subjects ( n  = 120) received single doses or multiple‐ascending doses of PF‐06648671/placebo for 14 days. No serious adverse events occurred; severe adverse eventswere deemed not drug related. PF‐06648671 decreased Aβ42 and Aβ40 concentrations in CSF, with greater effects on Aβ42, and increased Aβ37 and Aβ38 levels, particularly Aβ37. No significant change in total Aβ was observed. The PK/PD model well described the tendency of observed CSF Aβ data and the steady‐state effects of PF‐06648671, supporting its use for predicting central Aβ effects and optimal dose selection for GSMs in future trials.